Examining immersive audio’s role in flow and gaze behavior in pseudo-VR environments - Huang, Quncan; Li, Zhenzhen (Frontiers in Virtual Reality, 2025)
The audience’s sense of presence diminishes significantly when 360° videos are presented on a flat 2D screen. This study investigates whether immersive audio can compensate for the loss of visual immersion, enhancing viewers’ concentration and emotional engagement on non-VR devices. A key question is thus raised: when production resources are limited, should creators prioritize auditory or visual enhancement to improve the overall user experience? In order to answer this, we had 150 subjects watch several different types of video, some VR-like and others not, with sound either visualized on the ceiling or standard audio. Where possible, we monitored eye movement during viewing, and emotional involvement was assessed using a simple questionnaire afterwards. Results speak for themselves since implementing auditory improvement has been seen to increase involvement or concentration as well. In cases where only VR videos are provided, concentration and interest are not easily achieved. Therefore, we can conclude that in settings outside head-mounted devices, auditory qualities vastly outweigh visual enhancement if immersion is desired. This paper presents a simpler and more practical solution to the problem for creators of VR industrial material. It has been shown that even if using VR devices proves impractical or too costly, the population can greatly enhance the emotional effects of watching VR videos by focusing more on auditory technology. This presents a new mode of thought for producing products, which may enhance the solutions derived from wide usage and decrease the expense necessary for the advantages of an immersion product.